Genetics: - Klug, William S. (Prentice Hall, 2003)
This book is unique in that it takes a molecular first approach. It starts with DNA and moves through the genetic expression at the molecular level before turning to the more traditional Mendelian and Neomendelian transmission genetics. This book emphasizes what the reader should come to understand, not simply memorize. In addition to topics traditionally covered in genetics, this book provides cutting edge information on Bioinformatics and Proteomics, as well as a chapter on advanced topics in Molecular Genetics.